Effectiveness of Acetone and Aquadest Solvents on the Extraction of Acacia mangium Bark as Candidate Feed Additive - Sinaga, Desi Maria; Pertiwi, Vindo Rossy; Suryani, Heni; Santi, Melia Afnida; Maradon, Gusma Gama; Alamsyah, Alamsyah; Shobiiah, Nada (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2025)
This study aimed to determine the effectiveness of distilled water (aquadest) and 70% acetone as solvents in extracting bioactive compounds from Acacia mangium bark, which has potential as a feed additive. The extraction process was carried out using the reflux method with a solvent-to-sample ratio of 10:1 (w/v) at a temperature of 90–100 °C. The resulting extracts were then analyzed both qualitatively and quantitatively through phytochemical tests to identify the presence of secondary metabolites such as flavonoids, tannins, saponins, alkaloids, and phenolics. The extraction results showed that the yield of Acacia mangium bark extract using 70% acetone was 8,902%, whereas that using distilled water was 1,219%. The findings also indicated that 70% acetone produced extracts with higher phenolic compound content compared to distilled water. Furthermore, quantitative analyses of total tannin and total phenolic contents revealed higher values in the extracts obtained with 70% acetone than those with distilled water. Therefore, 70% acetone can be recommended as an effective solvent for extracting bioactive components from Acacia mangium bark using the reflux (heating) method, demonstrating its potential application as a natural additive source to enhance feed quality.